About the internet use in olive oil commercializacion. Sectorial analysis in Catalonia - Cristóbal Fransi, Eduard; Montegut Salla, Yolanda; Gómez Adillón, Maria Jesús (REVESCO. Revista de Estudios Cooperativos, 2016)
Cooperatives are organizations with great economic and social presence in Spain, and have a great influence on the rural economy. The main objective of this work is the analysis of the ICT uses by agribusiness cooperatives, focusing on the olive oil production to determine the main factors that influence in its behavior on the Web. In the present paper their websites are analyzed and determined what kind of information provides both general data as marketing. From the results, we search the possible relationship between the size of the cooperative, its export activity or ecommerce activity, using logistic regression. In this way we can know whether the implementation of new technologies in cooperatives really possible to develop an optimal economic activity.